Clathrin-adaptor ratio and membrane tension regulate the flat-to-curved transition of the clathrin coat during endocytosis - Delia Bucher (Nature Portfolio, 2018)
The sequence of structural and molecular events during clathrin-mediated endocytosis is unclear. Here the authors combine correlative microscopy and simple mathematical growth laws to demonstrate that the flat patch starts to curve when around 70% of the final clathrin content is reached.